Interindividual variability and lateralization of μ-opioid receptors in the human brain - Kantonen, Tatu; Karjalainen, Tomi; Isojärvi, Janne; Nuutila, Pirjo; Tuisku, Jouni; Rinne, Juha; Hietala, Jarmo; Kaasinen, Valtteri; Kalliokoski, Kari; Scheinin, Harry; Hirvonen, Jussi; Vehtari, Aki; et al. (NeuroImage (Orlando, Fla.), 2020)
Alterations in the brain’s μ-opioid receptor (MOR) system have been associated with several neuropsychiatric disorders. Central MOR availability also varies considerably in healthy individuals. Multiple epidemiological factors have been proposed to influence the MOR system, but due to small sample sizes the magnitude of their influence remains inconclusive. We compiled [11C]carfentanil positron emission tomography scans from 204 individuals with no neurologic or psychiatric disorders, and estimated the effects of sex, age, body mass index (BMI) and smoking on [11C]carfentanil binding potential using between-subject regression analysis. We also examined hemispheric differences in MOR availability. Older age was associated with increase in MOR availability in frontotemporal areas but decrease in amygdala, thalamus, and nucleus accumbens. The age-dependent increase was stronger in males. MOR availability was globally lowered in smokers but independent of BMI. Finally, MOR availability was higher in the right versus the left hemisphere. The presently observed variation in MOR availability may explain why some individuals are prone to develop MOR-linked pathological states, such as chronic pain or psychiatric disorders. Lateralized MOR system may reflect hemispheric work specialization in central emotion and pain processes. •Sex, age and smoking have regionally specific influence on human μ-opioid receptor (MOR) availability in the brain.•MOR availabilities have regional asymmetries between the two hemispheres, right hemisphere being more abundant in MORs.•Variability in MOR system may explain why some individuals are vulnerable to chronic pain and neuropsychiatric disorders.